2023
DOI: 10.1002/adbi.202200289
|View full text |Cite
|
Sign up to set email alerts
|

Dim Light at Night Promotes Circadian Disruption in Female Rats, at the Metabolic, Reproductive, and Behavioral Level

Abstract: Inhabitants of urban areas are constantly exposed to light at night, which is an important environmental factor leading to circadian disruption. Streetlights filtering light through the windows and night dim light lamps are common sources of dim light at night (DLAN). The female population is susceptible to circadian disruption. The present study is aimed to determine the impact of DLAN on female Wistar rats circadian rhythms, metabolism, reproductive physiology, and behavior. After 5 weeks of DLAN exposure da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 101 publications
0
1
0
Order By: Relevance
“…More chronic exposure to dim light at night (i.e., for at least 2 weeks) in male rats leads to increased lipid storage in the liver and severely impairs the daily expression of many metabolic genes in the liver and white adipose tissue [ 67 , 68 ]. Furthermore, chronic exposure to dim light at night in female rats flattens the rest–activity rhythm, reduces nocturnal food intake, blunts the estrous cycle, and triggers anhedonia [ 69 ]. In humans, a longitudinal study has revealed that long-term exposure to light during the night period is associated with increased atherosclerosis [ 70 ].…”
Section: Effects Of Circadian Rhythms On Metabolismmentioning
confidence: 99%
“…More chronic exposure to dim light at night (i.e., for at least 2 weeks) in male rats leads to increased lipid storage in the liver and severely impairs the daily expression of many metabolic genes in the liver and white adipose tissue [ 67 , 68 ]. Furthermore, chronic exposure to dim light at night in female rats flattens the rest–activity rhythm, reduces nocturnal food intake, blunts the estrous cycle, and triggers anhedonia [ 69 ]. In humans, a longitudinal study has revealed that long-term exposure to light during the night period is associated with increased atherosclerosis [ 70 ].…”
Section: Effects Of Circadian Rhythms On Metabolismmentioning
confidence: 99%